Pembuatan Grating Tahan Beban Truk Muatan Pasir atau Batu di Malang - Hadi, Syamsul; Witono, Kris; Kasijanto, Kasijanto; Purwoko, Purwoko; Muqit, Abd. (LPPM UNINUS, 2025)
Damage to the grating after being passed by heavy vehicles from trucks carrying hot asphalt during road repairs with asphalting of roads in residential areas is a problem faced. The purpose of community service is to obtain grating made of strong steel that can be passed by trucks loaded with stone or sand or asphalt with a full load and can be entered by rainwater and passed by heavy vehicles without sagging or damage, but can be opened and closed again if desired for cleaning or repairing water gutters. The method applied is a discussion with residents to determine the desired model design, make adequate gratings, install gratings, trials and modifications, and submit to the Head of RT 03 where the gratings are installed. With the installation of good gratings, it is hoped that the safety of residents or guest vehicles can be guaranteed in traffic in the area. Thus, there is synergy between the State Polytechnic of Malang (Polinema) and residents in order to realize safety in community life in RW 06 Tasikmadu, Lowokwaru, Malang City.